V+(-43/6)=21/3

Simple and best practice solution for V+(-43/6)=21/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for V+(-43/6)=21/3 equation:


V in (-oo:+oo)

V-43/6 = 21/3 // - 21/3

V-43/6-(21/3) = 0

V-43/6-7 = 0

V-85/6 = 0 // + 85/6

V = 85/6

V = 85/6

See similar equations:

| 11y-7-6y=6y-3 | | 65=30-5(x-4) | | 8/5d=40 | | 6x+(x-2)=180 | | 0.7(x-3)=14 | | 22-5x=8x-4 | | 0.8(x-3)=1.4 | | 4x-2=13x-52 | | (x-1)(x-2)(x+6)=60 | | 60+50x=1.3x | | X/5.7=8.5 | | x=25-22 | | 2n=167 | | 1x-2=2x-2 | | 48*10^18/4*10^4 | | 12/3/11/3 | | 2x+3/5=x | | x-9/8=4/5 | | x-3(2x+3)=11 | | 82-2x=16+20 | | 5/3/11/3 | | 136-4x=23x+16 | | x(3x-1)(3x+2)=0 | | 11a-3b=20 | | 48x10^14/4x10^4 | | F(x)=-3x^2-14x+24 | | 3/2d=27 | | 9=-2(9-3) | | V=18(8)(2) | | 3a-2=9 | | 9/5t=27 | | 5s^4+22s^2t+8t^2= |

Equations solver categories